Performance Analysis of QOS Parameters of 4 G – Long Term Evolution (LTE) Based Architecture for M - Health Application - Rangankar, Suresh; Mhala, Nitiket (International Journal of Advanced Science and Technology, 2019)
Now a day’s wireless communication technologies are the important part of the broadband infrastructure of countries for the different applications. Due to limitations on the coverage in wired technologies, wireless technologies become more advantageous & successful to support remote health services. Also due to development in mobile technologies, medical services become the new generation of health care systems. The wireless technologies are used for improving the operating way of health care services and the conditions for the users. Ability of wireless technologies to transmit differentiated services is essential for the deployment of networks for m Health applications. For effective utilization of network, identification & different requirements in real time application such as bio medical signals need to be considered. Wireless data networks, particularly 4th generation (4G) and long-term evolution (LTE) are rapidly growing which in response to its increasing popularity and penetration of mobile devices among individual, corporate, business, and government service consumers. This wireless data networks, particularly 4th generation (4G) and long-term evolution (LTE) are rapidly gaining ground as predominant telecommunication services to provide high quality services to different applications particularly in health care system. However the quality of service (QOS) is the important factor in successful adoption of such wireless communication technologies in national/international scope specifically in health care system. Also due to rapid development in the features and capabilities of smart phone devices, wireless network technologies, plays important role in of Mobile Health domain (m-Health). In m health, body area network is the key interfacing network. Body area network (BAN) which consists of different biological sensors implanted on the human body which collects different medical data & send it to network by using smart phone devices. Hence sometimes this interfacing architecture of wireless body area network with wireless 4G network with the use of smart phones for health care system is referred as next generation health care system.